"Yes or No? What do Lithuanian Unemployed Young People Think about Employment in Elderly Care Sector?" - Okunevičiūtė Neverauskienė, Laima; Žalimienė, Laimutė; Junevičienė, Jolita (Calitatea Vieții, 2024)
The aim of the research is to investigate unemployed young people’s opinions about work and the workplace in the elderly care sector in Lithuania. The key theoretical concepts of the study are public service motivation (PSM), work meaningfulness and gendered approaches. Quantitative research methodology was chosen to gather the empirical data. The respondents of the survey, which was carried out in 2022, were young unemployed people (aged 18–29) registered in the Lithuanian Employment Service database. The rationale for this analysis is growing demand for labour force in the elderly care services, and fairly significant proportion of NEET youth in Lithuania and other EU countries. Various initiatives globally and particularly in the countries of Europe reveal that if to find ways how to attract this underutilised workforce to the elderly care sector, this could be one of the employment alternatives for young unemployed people. Therefore, the attitudes of the young unemployed people towards workplace in elderly care can be utilised searching how to improve effectiveness of employment services. Our study revealed that young unemployed people in Lithuania agree that work in elderly care sector is valuable and meaningful work to the society, however they see work in elderly care as physically and emotionally demanding, unqualified and low-paid. If youth would have to work temporarily in elderly care, they would prefer working for more independent elderly people.